Waste Management Strategy of the Free Nutritious Meal Program (Makan Bergizi Gratis, MBG) to Realize SDGs 12 Responsible Consumption and Production: A Case Study of Sleman Regency - Priyaji Agung Pambudi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Sleman Regency has successfully reduced municipal waste generation from 650 g/capita/day in 2019 to 496.27 g/capita/day in 2025, a 23.65% reduction that places it slightly below the average waste generation rate for middle-income countries (500–700 g/capita/day). However, the implementation of the Free Nutritious Meal Program (Makan Bergizi Gratis, MBG) is expected to create new environmental challenges through increased organic waste generation. This study aims to assess the projected waste generation from MBG and formulate a sustainable waste management strategy for Sleman Regency. The research employed a literature review, regional waste data analysis, quantitative estimation of waste generated per meal portion, and scenario analysis using Business-as-Usual and circular economy interventions. The findings indicate that 66 Nutrition Fulfillment Service Units (Satuan Pelayanan Pemenuhan Gizi, SPPGs) serving 251,356 beneficiaries are projected to generate approximately 21.95 tons of organic waste per day, or 5,707 tons annually, representing about 2.67% of Sleman's total annual waste generation. This additional waste may increase environmental pressure, pest and disease vectors, and methane emissions if disposed of without proper segregation. Therefore, source reduction, waste segregation, composting, biodigesters, and maggot cultivation, supported by strong multi-stakeholder collaboration, are essential to promote a circular economy, support Sleman's low-carbon development, and contribute to SDG 12 (Responsible Consumption and Production).